Review on extraction methods of essential oil from kaffir lime (Citrus hystrix) leaves / Mazlin Mohideen ... [et al.] - Mohideen, Mazlin; Idris, Mohamad Iqbal Hazmie; Zainal Abidin, Nor Syamimi Izzati; Kamaruzaman, Nur Azzalia (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Kaffir lime or “limau purut” (Citrus hystrix) is a popular traditional herbal plant with aromatic leaves. It produces fruits which are commonly used in Asian cuisines as a flavouring agent. Essential oil has been a popular and valuable product applicable in various industries, but its availability is scarce. Essential oil from the leaves of Citrus hystrix is a complex mixture of volatile and semi-volatile compounds. It is rich in bioactive molecules that act synergistically to improve the well-being of an individual. Essential oil is extracted from Citrus hystrix leaves using a few extraction methods; however, the most excellent extraction methods have yet to be ascertained. This review paper highlights several extraction methods that determined the final yield of Citrus hystrix leaves’ essential oil and the comparison of advantages and disadvantages between each method. Two types of methods are discussed, which are conventional and modern methods. Conventional methods include hydro-distillation, steam distillation, Soxhlet distillation and solvent extraction, while the modern method includes pressurized liquid extraction (PLE). In addition, pretreatment processes are also included as they can significantly affect the performance of other important processes and production yield. This paper also found that the highest yield of 56.16% was obtained using PLE method. Essentially, each of the extraction and pre-treatment methods has its own pros and cons; hence choosing a suitable method depends heavily on the producer's demand and requirement.